Gambaran Klinis dan Histopatologi Keratosis Seboroik : Clinical and Histopathological Features of Seborrheic Keratosis - Mayati Suwoko, Wika Umayatul Choiroh; Yuniaswan, Anggun; Retnani, Diah (Jurnal Klinik dan Riset Kesehatan, 2023)
Seborrheic keratosis is the most common benign epidermal tumor and is often found in the elderly, which is about 20% of the total population. The exact cause of this disorder is still not clearly known. Sun exposure is said to be one of the causes of seborrheic keratosis. Lesions can be flat, circumscript and dull-looking brown spots, with a smooth, velvety surface, can also take the form of hyperpimented papules or plaques, round or oval, circumscript, such as coated wax (waxy) with a verrucosa surface, or a picture of sticking "stuck on" to the surface of the skin. skin. Seborrheic keratosis can be in the form of multiple, solitary, disseminated lesions in old age, dermatosis papulosa nigra and also in the form of Leser-Trelat signs. The diagnosis of seborrheic keratosis is made through anamnesis, physical examination and by histopathological examination. There are various histopathological features of seborrheic keratosis, this literature review aims to explain the various clinical features of seborrheic keratosis along with their histopathological features and can assist readers in determining the type of seborrheic keratosis when they come across such cases.